Green Hospital Concept: Its Challenges, Benefits and Focus Areas - Giasuddin, Abu Sayed Mohammad; Shahjahan, Mohammad; Seoty, Nuhad Raisa (British Journal of Healthcare and Medical Research, 2024)
We need to understand what actually a green hospital means. The concept of 'Green Buildings' can be traced to the United Nations concerted efforts, over the years, to bring to the fore the idea of sustainability in all aspects of human development. The concept of developing sustainable green buildings received further attention with the introduction of Triple Bottom Line (TBL) approach. According to TBL approach, primary goal of designing a green building would be to reduce the use of resources such as land, water, energy and supplies. The noble idea is for the people so that who live, work, learn and heal in green buildings are healthier, happier and more productive. Therefore, a sustainable green hospital enhances patient wellbeing, aids in curative process while utilizing natural sources in efficient environment friendly manner. A green hospital chooses an environment friendly site, utilizes efficient designs, uses green building materials, thinks green during construction around a facility that recycles, reuses materials, reduces waste and produces cleaner air, reduce CO2 generation etc. The standards and strategies are developed and laid down by World Green Building Council (WGBC), US Green Building council (USGBC) and the leadership in Energy and Environmental Design (LEED) since green hospital movement began years ago. The requirements, challenges and barriers for setting up a green hospital with proper concept and design are reviewed in the present article.